Kejawen: Kearifan Yang Adiktif - Krisna Sukma Yogiswari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
There are six recognized religions and growing in Indonesia, besides that there is also a growing local trust and co-exist in the lives of its people. Is Kejawen, one of the local wisdom archipelago that developed in Java. Its existence up in the postmodern age is enough to get attention, Karl Marx criticize religion as an opiate of the people, and bring it within alinenasi, development Kejawen always steady to date and changes in the pattern of community life that have started to develop and leave the spiritual things, and doctrine which raises curiosity. The highlight teachings and doctrine is manunggaling kawula Ian gusti and sangkan paraning who is also a belief Keratoon Palace almost all of Java. If explored further Kejawen doctrine resembles the Hindu-Buddhist doctrine, which in its development even further is a syncretism between Islam and Hindu-Buddhist.